Treatment of age related macular degeneration (AMD) currently and in the past - Klaudia Brożyna; Jędrzej Tkaczyk; Katarzyna Baltaziak; Krystian Ciechański; Lucyna Baltaziak; Robert Rejdak (Kazimierz Wielki University, 2018)
Age-related macular degeneration (AMD) is a disease that blurs the sharp, central vision you need for "straight-ahead" activities such as reading, sewing, and driving. AMD affects the macula, the part of the eye that allows you to see fine detail. AMD causes no pain. AMD is an irreparable disorder, which mostly occurs among people after 50. Nowadays the pathogenesis of AMD is still not entirely clarified, however this disorder has multifactor background, which include interactions between genetic and environmental factors. AMD is divided into two forms: exudative ("wet") and nonexudative ("dry"). The treatment of age-related macular degeneration depends on the stage of the disease progression. One of the first methods of treatment of exudative AMD was laser photocoagulation with argon laser. Currently, this kind of treatment is used in certain cases of neovascularization in extrafoveal area. Next elderly method of therapy of AMD was a photodynamic therapy (PDT) at year 2000. The treatment consist in intravenous injection of verteporfin and a laser at the same time. At 2002 was in use transpupillary thermotherapy (TTT). Last few years for treatment AMD is used antagonist of vascular endothelial growth factor (VEGF). We distinguish: pegatanib, ranibizumab, bevacizumab and aflibercept. Nowadays all of available methods do not eliminate causes of that disorder and in this connection currently treatment is still symptomatic. Apart from every mentioned method above, nutritional therapy is also essential and it decrease the risk of progression of AMD. The diet should contain products full of vitamin C,E, beta carotene, zinc and copper.